Estudo Comparativo do Efeito Larvicida de Extratos de Frutos Verdes e Maduros de Melia azedarach L. (Sapindales: Meliaceae) em Aedes aegypti L. (Diptera: Culicidae) - Prophiro, Josiane Somariva; Rossi, Juliana Chedid Nogared; Kanis, Luiz Alberto; dos Santos, Tania Gonçalves; da Silva, Onilda Santos (BioAssay, 2009)
The insecticidal activity of Melia azedarach L. (Sapindales: Meliaceae) in insects of agriculture importance have been extensively evaluated. However, the possibility of the use of this plant in the control of insects of medical importance is poorly studied. The aim of this work was to compare the larvicidal effect of ethanolic extracts of unripe and ripe fruits of M. azedarach on Aedes aegypti (Linnaeus, 1762) (Diptera: Culicidae). The results showed that both extracts of unripe and ripe fruits of M. azedarach caused larval mortality. The lethal concentrations (LC50, LC90 e LC95) obtained from unripe fruits were 0.08%, 0.31% and 0.47% respectively to 3º instar and 0.18%, 0.43% and 0.55% respectively to 4º instar of A. aegypti after 48h exposition. In relation to the ripe fruits the LC50, LC90 and LC95 were 0.05%, 0.10% and 0.12% respectively to the 3º instar and 0.05%, 0.11% and 0.14% respectively to the 4º instar, after 48 h of exposition. These results showed that ripe fruits are more effective than unripe fruits for controlling A. aegypti larvae.